Students’ Engagement with Mental Disability Knowledge and Theory in the Writing Classroom: Implications for Transfer Research - Little, Hunter (My University, 2025)
Drawing on data from a 10-week, classroom-based, qualitative study, this dissertation investigates students’ micro-level processes of transferring knowledge about mental disability from a critical disability studies perspective in a general writing course. The study was conducted at the University of Washington within my self-designed and taught Intermediate Expository Writing course which was meant to build students’ critical disability literacy. This study builds on the work of disability studies, writing studies, uptake theory, and knowledge transfer scholars, including the ongoing and prominent conversations about knowledge transfer in writing studies as well as theories of students’ boundary-work. The results demonstrate that students’ engagement with mental disability knowledge and theory in the writing classroom is deeply informed by their incoming relationships with the subject matter and the innumerable interactions that occur between students’ experience, each other, concepts, readings, writing tasks, and material space/place. Student writing, survey, and interview data were analyzed using thematic and discourse analysis and within the framework of Dylan Medina’s (2017) concept of micro-transfers or moment-to-moment interactions which inform how students define people, places, and things. Tracing such micro-transfers revealed how students uniquely take up and adapt knowledge about mental disability within a single course and across writing tasks. Through this analysis, I present five themes that help complicate traditional understandings of knowledge transfer as broad, easy-to-see translations of knowledge across contexts. The analysis illuminates the unique shifts in students’ relationships to disability, their dynamic process of adapting knowledge about disability, the impact of class environments on knowledge transfer, students’ need for alternative pathways for engaging with difficult concepts, and the potential of courses centered around critical disability studies to support student advocacy stances. These findings illustrate the use of micro-transfer as a framework for the analysis of knowledge transfer and course design and the benefits of incorporating critical disability studies discourse into general writing courses. To close, I offer implications for transfer, writing, and disability studies research; teaching; and writing program administration.
Thesis (Ph.D.)--University of Washington, 2025
Keywords: composition; disability studies; knowledge transfer; micro-transfer; rhetoric; writing studies; Rhetoric and Composition; Disability studies; Language; English